Groundwater hydrology of springs : engineering, theory, management, and sustainability - Krešić, Neven; Stevanović, Zoran (Butterworth-Heinemann/Elsevier, 2010)
Groundwater Hydrology of Water Resource Series Water is an essential environmental resource and one that needs to be properly managed. As the world places more emphasis on sustainable water supplies, the demand for expertise in hydrology and water resources continues to increase. This series is intended for professional engineers, who seek a firm foundation in hydrology and an ability to apply this knowledge to solve problems in water resource management. Future books in the series are: Groudwater Hydrology of Springs (2009), Groudwater Hydrology of River Basins (2009), Groudwater Hydrolog.